CORPORATE SOCIAL RESPONSIBILITY (CSR) BERBASIS SUMBER DAYA ALAM DIKABUPATEN PROBOLINGO - Askandar, Ach. Syamsul (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
Abstract One Of The Goals Of The State As Mandated By The 1945 Constitution Of The Republic Of Indonesia Is To Improve The Welfare Of The People. Based On Law Number 40 Of 2007, It Is Affirmed That Companies Carrying Out Their Business Activities In The Field Of Natural Resources And Or Fields Related To Natural Resources Are Obliged To Carry Out Social And Environmental Responsibilities In Probolinggo District. The Functions And Authorities Of The Regional Development Planning Agency (BAPPEDA) And The Constraints Faced. The Regional Government Forms A Facilitation Team Which Is Determined By The Decree Of The Regent. The Facilitation Team Is Tasked With: Conducting An Inventory Of Companies That Are Required To Implement The CSR Program, Conducting An Inventory Of CSR Proposals Based On The Development Priority Scale That Can Be Funded By CSR, Synchronizing, Harmonizing And Integrating The CSR Program With Regional Development Priority Programs, Together With FKTSP, Establishing A List Of Priority Program Proposals CSR, Which Will Be Submitted To The Company, Monitors And Evaluates The Implementation Of The CSR Program Together With FKTSP, Conducts An Assessment Of The Company Implementing The CSR Program As A Material For The Regent's Consideration In Awarding The Award. Keywords:CSR Probolinggo Regency Company